Lincoln ebook A photobiography. - Freedman, Russell (2020)
The Newbery Medal–winning book for young readers presents “a human portrait of a politician honorably confronting the most vexing issues of his era” ( The New York Times Book Review ).   Abraham Lincoln stood out in a crowd as much for his wit and rollicking humor as for his height. This Newbery Medal-winning biography of our Civil War president is warm, appealing, and illustrated with dozens of carefully chosen photographs and prints.   Russell Freedman begins with a lively account of Abraham Lincoln's boyhood, his career as a country lawyer, and his courtship and marriage to Mary Todd. Then the author focuses on Lincoln’s presidency, skillfully explaining the many complex issues he grappled with as he led a deeply divided nation through the Civil War. The book's final chapter is a moving account of his tragic death at Ford's Theatre on April 14, 1865. The volume concludes with a sampling of Lincoln writings and a detailed list of Lincoln historical sites.   "Few, if any, of the many books written for children about Lincoln can compare with Freedman's contribution…This is an outstanding example of what (juvenile) biography can be. Like Lincoln himself, it stands head and shoulders above its competition." — School Library Journal